Digital human modeling : applications in health, safety, ergonomics, and risk management : ergonomics and design : 8th International Conference, DHM 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, proceedings /: applications in health, safety, ergonomics, and risk management : ergonomics and design : 8th International Conference, DHM 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, proceedings. (2017) - Unknown
No abstract available